Men's Sports or Women's Sports?: Gender Norms, Sports Participation, and Media Consumption as Predictors of Sports Gender Typing in China. (April 2021) - Xu, Qingru; Fan, Minghui; Brown, Kenon A.
In this study, we explored the perception of sports based on gender norms in China. Applying social cognitive theory, we surveyed 423 Chinese respondents about their gender perceptions of 16 sports. Results revealed four distinct categories—masculine, lifestyle, neutral, and feminine—and that men tended to rate sports as significantly more masculine than women. Overall, gender role beliefs, sports participation, and sports media consumption all significantly correlated with individual gender typing of sports. The findings of this study, which is based on findings from Hardin and Greer and is one of the first quantitative studies about gender perceptions of sports in China, shed light on the role that gender norms play in shaping the country's sports landscape. Theoretical and practical implications are discussed.